THE BINDING POWER OF GOVERMENT RULES LAWS AND RESTRICTION TO SOCIETY BASED ON CONSTITUTION (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2022)
The purpose of this research is to offer an update on the position of PPKM policies issued by the Indonesian government in a precise and binding manner. Using normative research with the aim of answering issues based on the scientific side. From this research, the researcher offers that our country adheres to a system where legal norms are tiered where a lower norm is sourced, applies, and is based on a higher norm in accordance with a hierarchical arrangement where lower regulations may not conflict with higher regulations. In the wake of the COVID-19 pandemic, the government must immediately adjust the PPKM policy with the hierarchical arrangement of laws and regulations. This is because a policy that does not have a legal instrument or forum that is not included in the category of statutory regulations has a bias binding power where this is because the PPKM policy is contained in a rule in the form of a policy regulation, not a statutory regulation.